Relationship of Knowledge and Attitude of Parents with The Provision of Basic Immunization in Baby in Puskesmas Alalak Selatan Kota Banjarmasin - Utami, Syahrida Wahyu; Lestari, Nur Cahyani Ari; Purwanti, Sri (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
The immunization program is carried out so that the baby gets all five types of immunizations in full, so that the baby is protected from diseases that can endanger the baby's health. Knowledge about immunization is very important for mothers, especially mothers who have just given birth to their babies. Immunization is giving vaccines to toddlers so that the immunity of the toddler's body can be increased and immune to disease. The research objective to be achieved based on the above problem formulation is to determine the relationship of knowledge and attitudes of parents with basic immunization for infants at the Alalak Selatan Health Center in Banjarmasin City in 2018. The research design used in this study is descriptive analytic research. using an accidental sampling technique approach by taking respondents who came to the South Alalak Health Center. The sample used in this study were 79 respondents, with data analysis using the Chi Square test. The results showed the relationship between knowledge and immunization based on chi square test data regarding the relationship of knowledge with basic immunization, obtained a significance of 0.004 < 0.05, this concludes that there is a relationship between knowledge and basic immunization. the relationship between parental attitudes with basic immunization based on the chi square test output data obtained significant by 0,000 < 0.05 meaning that there is a relationship between parental attitudes and basic immunization. Alalak Selatan Community Health Center should increase socialization on the importance of basic immunization for children through electronic media as well as health center staff and health networks under its auspices.